A Review of Ocean Dynamics in the North Atlantic: Achievements and Challenges - Knut Lehre Seip (Climate, 2020)
I address 12 issues related to the study of ocean dynamics and its impact on global temperature change, regional and local climate change, and on the North Atlantic ecosystem. I outline the present achievements and challenges that lie ahead. I start with observations and methods to extend the observations of ocean oscillations over time and end with challenges to find connections between ocean dynamics in the North Atlantic and dynamics in other parts of the globe.